Global warming reports: a critical overview of IGOs publications - Ascione, Laura (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility, and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban planning literature review section presents recent books and journals on selected topics and issues within the global scientific panorama. For the first issue of TeMA Journal volume no. 18, this section provides a critical overview of recent reports and documents on climate change, published by different types of stakeholders. This review examines the landscape of climate change reporting through a comparative lens, focusing on key findings, strengths, weaknesses, and implications of selected publications. This contribution aims to examine reports produced by International Governmental Organizations (IGOs), analyzing their approach, findings, and potential limitations.